Effect of egg yolk on thawed semen quality of paco (Piaractus brachypomus) - Manrique Quispe, Yan (2023)
The objective of the study was to evaluate the effect of the type of egg yolk (quail-YC vs hen-YG) on the quality of frozen paco (Piaractus brachypomus) semen (volume, colour, concentration, motility, vitality and fertility). Eighteen breeders (15 males and 3 females) were used, whose spermiation and ovulation, respectively, were induced with carp pituitary extract. Semen was collected by massaging the abdomen of the fish. Fresh semen was evaluated and then diluted with a cryoprotective solution that included YC or YG. Diluted semen was frozen and thawed at 30 days for post-thaw evaluation and fertility testing. A notable decrease in seminal parameters was found due to the effect of freezing. Motility was lower for YC compared to YG (14.8 vs. 18.8%; p<0.05), while vitality (31 vs. 28.8%), activation time (1.4 vs. 1.3 min) and fertility (18.4 vs. 20.4%) were similar between groups. In conclusion, the motility was improved with the addition of chicken egg yolk, while the vitality, activation time and fertility were not influenced by the type of yolk.